Pengaruh Partisipasi Anggaran terhadap Kinerja Manajerial dengan Motivasi Kerja Sebagai Variabel Pemoderasi - Iqbal Maulana; Henri Agustin; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2020)
This study is a study that examines the effect of budget participation on managerial performance with work motivation as a moderating variable in public sector organizations in the Regional Work Units (SKPD) of Pesisir Selatan Regency at 2020. This study used a questionnaire survey method that was distributed to SKPD officials. The sampling technique was purposive sampling method. The data analysis technique uses the Moderated Regression Analysis (MRA) method. The results showed that: 1). Budget participation has a negative effect on managerial performance, 2). Pursuing motivation strengthens the effect of budget participation on managerial performance